Um método para transcrição de termos biomédicos e um protótipo de ferramenta didática para ensino de lógica em ontologia aplicada - Guilherme Francis de Noronha (2017)
The field of applied ontology is increasing due to modernization of information systems and need of its semantization, that includes from specialist domains to the web. So is done a great effort to formalize the contents in a way that allow it be processed by computers and transform explicit information into implicit one. Nevertheless, the building process of ontologies needs an effort that requires interdisciplinarity of the responsible staff, because it involves specialist knowledge. In additionto the knowledge of applied ontology, the science information professional needs to count on knowledge from information systems and technology, knowledge from descriptive logic and support from a specialist in the realm to be built. Only with the support of these three bases will be possible to build an ontology well-grounded which attends all requisites of information representation. However, is realized thatscience information professionals not always do courses that teach the logical content that involves ontologies construction. The logic belongs to the core of ontology theory, but its not used in a suitable way to improve its potential. Therefore this work is an initiative to elucidate the use of logic in ontology based systems. To reach that, it was created a method of transcription of formal definitions based in description logic used by ontologies. The validation of the method was tested with the transcriptions of some definitions of Blood Ontology and checked with help of reasoners. Furthermore, it was proposed an online system (called OntoLogica) to help the teaching of logic in applied ontology systems. OntoLogica, which was prototyped, will help its users to create and transcript formal definitions to logic using the method proposed in this work. The results of the transcriptions made generated correct and also incorrect inferences. The conclusion of this work was thetranscriptions are important because they acquire new knowledge, but the field still needs cautions to define and transcript formal definitions.